The Effect Of Non-Physical Work Environment, Work Load and Compensation on Turnover Intention at PT. OKI Pulp & Paper Mill - Dede Hadi Widianto; Zunaidah - Zunaidah; Afriyadi Cahyadi (At-Tadbir : jurnal ilmiah manajemen, 2026)
This study investigates the the effect of non-physical work environment, work load and compensation on turnover intention at Pt.OKI Pulp & Paper Mills. Conducted in a private sector company PT.OKI Pulp & Paper Mills in South Sumatra Province, data was collected from employees using a quantitative survey approach and analyzed with multiple linear regression model. Sample was taken using  probability sampling, cluster sampling on 4 supporting departments so that 111 employees was obtained. The results showed that The non-physical work environment does not significantly influence turnover intention, workload has a positive and significant effect on turnover intention and compensation has a negative and significant effect on turnover intention. Also simultaneously, The non-physical work environment, workload, and compensation simultaneously have a significant effect on turnover intention